On income and wealth inequality in Turkey - Orhan Torul; Oguz Oztunalı (Central Bank Review (CBR), 2018)
In this paper, we study Turkey's income and wealth distribution using a model-based approach via a modified Aiyagari (1994) model. In doing so, we use recent parameter estimates for Turkey and calibrate our model to match Turkey's income and wealth inequality measures. We document that our calibrated model matches Turkey's empirical economic inequality metrics with high precision, therefore can be used to infer Turkey's wealth distribution, which lacks data and detailed analysis. We compare Turkey's inequality measures with other countries, and display that by any conventional metric, Turkey qualifies as one of the more unequal economies. Finally, we quantify the welfare cost of inequality, and report that in order not to switch to the unequal Turkish economy, a utilitarian benevolent planner of Turkey's counter-factual representative-agent economy would be indifferent to forgoing 25.15% of steady-state consumption along with working an extra 33.61% of steady-state hours indefinitely.
Keywords: 330; Heterogeneous-agent; General equilibrium model; Incomplete markets